Pengelolaan Keuangan Keluarga Penerima Manfaat Program Keluarga Harapan (PKH) di Desa PangkungParuk, Kecamatan Seririt - Wayan Yudiarsana; Kadek Rai Suwena (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
This study aimed to examine financial management patterns, the utilisation of assistance, and the impact of the Family Hope Programme (Program Keluarga Harapan/PKH) on the welfare of beneficiary families in Pangkung Paruk Village, Seririt District. This study employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation and were analysed qualitatively. The findings show that household financial management among PKH beneficiary families is predominantly managed by wives, but it remains simple and lacks systematic planning. PKH assistance is mainly used to meet basic family needs, particularly education and health. The PKH programme helps reduce household economic burdens; however, it does not fully promote economic independence among beneficiary families. Therefore, efforts to strengthen financial management capacity are needed to support sustainable family welfare.